Adam Mickiewicz: "Widzenie" - Duk, Józef (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
The unique value of Mickiewicz’s “Vision” is its included image of the structure of the supernatural order. The poet described is as an infinite, continually spreading space, spherical in shape and filled with a luminous divine element penetrating everything most easily, in the middle of which there is an eternally sinking well that emits out that element. The well emitting the luminous transparent matter is God Himself. Contrary to Christian dogmas He is obviously de-anthropomorphised but not de-animated, as also in that form He means the source of life and love. In ecstasy, the experiencing individual adopted godly attributes: he united with the material-spiritual being that continually came out of God, and he found himself in the centre of the universe where he was given the ability of receiving all its movements and signals, and at the same time — the privilege of being everywhere. According to Mickiewicz’s “Vision”, eternal life has an active and creative nature - it is characterised by supply of the animating love element, endless development and growth, the grace of eternal watching the transcendental reality, excellent contact with Creator, and the gift of creation. The second fragment of the “Vision” reveals valuable information on the nature of extrasensory perception. It is absolute, free from any difficulties, prompt and insensible; it is perfect perception.